2022
DOI: 10.1039/d2cp03185j
|View full text |Cite
|
Sign up to set email alerts
|

Iodine speciation in deep eutectic solvents

Abstract: Iodine has been shown to act as a good electrocatalyst for metal digestion in deep eutectic solvents (DESs) but little is known about its speciation or reactivity in these high...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 60 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…Previous work has shown that iodine forms I 2 Cl − and I 3 − complexes in EG : ChCl with no additional water. 27 The presence of water or different ethylene glycol content may affect the formation of these species, as the solubility of iodine in ethylene glycol is 0.28 mol dm −3 , whereas the solubility in water is only 1.32 × 10 −3 mol dm −3 when no additional complexing agents are present. 43 Therefore, extended X-ray absorption fine structure (EXAFS) spectroscopy was carried at the iodine K-edge out on samples containing nominally 0.1 mol kg −1 iodine, with the DES containing a range of water contents up to 20 wt%, and also for four different molar ratios of EG : ChCl.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown that iodine forms I 2 Cl − and I 3 − complexes in EG : ChCl with no additional water. 27 The presence of water or different ethylene glycol content may affect the formation of these species, as the solubility of iodine in ethylene glycol is 0.28 mol dm −3 , whereas the solubility in water is only 1.32 × 10 −3 mol dm −3 when no additional complexing agents are present. 43 Therefore, extended X-ray absorption fine structure (EXAFS) spectroscopy was carried at the iodine K-edge out on samples containing nominally 0.1 mol kg −1 iodine, with the DES containing a range of water contents up to 20 wt%, and also for four different molar ratios of EG : ChCl.…”
Section: Resultsmentioning
confidence: 99%
“…26 It has recently been determined that the HBD plays a critical role for the species of iodine that are formed in DES media, with three general speciation types observed: mixed I 2 Cl − and I 3 − , mixed I 2 and I 3 − , and I 3 − alone. 27 The amount of I 2 Cl − present was linked to the activity of the chloride anion, with high chloride activity resulting in higher amounts of I 2 Cl − . The chloride activity itself is related to the strength of the interactions between chloride and the HBD used.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of iodine, it has been reported that both [I 2 Cl] − and [I 3 ] − are stable in ChCl: 2EG eutectic mixture (distribution between complexes tending to change as function of water addition) 81 , 82 , suggesting that both species should be able to oxidise iron according to Eqs. ( 7 , 8 ).…”
Section: Resultsmentioning
confidence: 99%
“…111 They also have inherently high concentrations of ligands, permitting the chemical oxidation of noble metals such as gold, [112][113][114] or palladium. 115 Alternatively, the ionic environment can stabilise oxidising species such as iodine 116 or bromine 117 without the need for additional anions that would be required in aqueous media.…”
Section: State Of the Art Of The Recycling Techniquesmentioning
confidence: 99%